Documents relating to the British military in India and the Anglo-Sikh War - Gough, Hugh Gough, Viscount, 1779-1869 (1850)
Includes examination of Hugh Gough by the Select Committee on Indian Territories (1852-1853), regimental returns, field state of the garrison at Dublin, notices from War Office, and statement regarding European residents in India, 1850-1854.
Keywords: Gough, Hugh Gough, -- Viscount, -- 1779-1869; East India Company; Sikh War, 1848-1849; India -- History -- British occupation, 1765-1947